Structural Effects of Seismic and Wind on Tall Buildings: A Review - Sanjay Raut*, Deepika Nair, Dhiraj Agrawal, Mohan Pidurkar (International Journal of Advanced Science and Technology, 2020)
With the increase in population, the lack of space in cities becomes the main issue. Due to this limitation in space, the constructions of tall buildings have become the necessity of time. The design criteria for tall buildings are very complex in comparison to low and mid-rise buildings. When a tall building is considered, it is exposed to static as well as dynamic loading. The life of a tall building is affected by various parameters such as bending, shear, torsion, drifts etc. and these effects have to be considered while analyzing and designing it. This paper presents a comprehensive literature review focusing on the structural response of tall buildings during wind and earthquake. This would help in the better understanding of various aspects of tall buildings when subjected to seismic and wind forces.